2018
DOI: 10.1108/jhtt-02-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

The effect of promotional mix on hotel performance during the political crisis in the Middle East

Abstract: Purpose This paper aims to investigate the effects of promotional mix in terms of advertisement, website and direct sale on job performance during the political crisis in the Middle East. Design/methodology/approach Data were collected from 121 Jordanian employees working in hotels in Aqaba city, using a self-administrated questionnaire including 35 items. Multiple regression analysis was conducted to test the research hypotheses. Findings The results of the current study revealed that there is a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 62 publications
2
26
0
Order By: Relevance
“…Leung and Lam [49] noticed that the hotel industry is not equipped with tools to deal with the crisis; therefore, managers play a key role. They are responsible for strategy, new procedures and guidelines for staff or communication [49], and for stimulating creativity and innovation, looking for new ideas of promotion [50]. Interestingly, the crisis might reveal a turning point for hotel enterprises looking for new competitive advantages [41,51].…”
Section: Consequences Of the Covid-19 Pandemic For The Hotel Industrymentioning
confidence: 99%
“…Leung and Lam [49] noticed that the hotel industry is not equipped with tools to deal with the crisis; therefore, managers play a key role. They are responsible for strategy, new procedures and guidelines for staff or communication [49], and for stimulating creativity and innovation, looking for new ideas of promotion [50]. Interestingly, the crisis might reveal a turning point for hotel enterprises looking for new competitive advantages [41,51].…”
Section: Consequences Of the Covid-19 Pandemic For The Hotel Industrymentioning
confidence: 99%
“…The quantitative analysis of the DEA scores using LINGO software showed examples in which hotel result in relatively high performance and in which year (2009 and 2011). What the results clearly showed is that the ability of hotels to succeed will not be determined by marketing factors, as assumed by Masa'deh et al (2018) or external factors such as crises (Bougatef, 2017). Nevertheless, hotel performance is affected here in this case study by their costs, the number of employees and food and beverage revenue as being clear in the DEA output of table 5.…”
Section: Discussionmentioning
confidence: 62%
“…Considering performance prior studies in relation to hotel's operation, many academics expressed it in an economic equation (Jones & Siag, 2009;Kilic & Okumus, 2005;Sigala et al, 2005) as a relationship between outputs and inputs. The main difference of the meaning of performance between manufacturing and service approach is that as a system, manufacturers focus on reducing resources or inputs to ensure production efficiency (Masa'deh, Alananzeh, Tarhini, & Algudah, 2018). However, service providers look at the main aim of their system or the outputs to ensure the quality of doing things (Effectiveness) approach (De Pelsmacker, van Tilburg, & Holthof, 2018).…”
Section: Performance Dilemma In the Egyptian Hotel Industrymentioning
confidence: 99%
“…Promotional tools and strategies aiming to attract the public should be properly and systematically planned to ensure that marketing activities are effective and productive (Masa'deh et al, 2018). Past studies indicated the prominent role of promotion for a product, service, or idea (Qian et al, 2019;Siddhanta & Banerjee, 2014;Untari et al, 2019).…”
Section: Introductionmentioning
confidence: 99%